(untitled) (Web of Teachers: Inderscience Research, 2025)
This article is devoted to the lexical phenomena of antonymy and synonymy. It examines the concepts of antonyms and synonyms, their role in language, as well as classification criteria. Antonyms are words that have the opposite lexical meaning, while synonyms are words that are close or identical in meaning. Both of these phenomena play an important role in enriching speech, creating expressive texts, and expressing thoughts more accurately.